2018
DOI: 10.22270/jddt.v8i6-s.2111
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cynodon dactylon on the haematological parameters and haematocrit of grass carp Ctenopharyngodon idella (Val.)

Abstract: The present study is aimed to investigate the effect of Cynodon dactylon on the haematological parameters of freshwater fish Ctenopharyngodon idella. The study reveals that there was a slight variation noticed in total serum protein, globulin, albumin, glucose, cholesterol and triglycerides. There was a significant variation observed in Red blood corpuscles (RBC), White blood corpuscles (WBC), Haemoglobin (Hb), MCH, MCHC, PCV in the blood of grass carp fed with control and Cynodon dactylon mixed diet. The prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The lack of a significant effect of C. dactylon extract on plasma viscosity, while reducing whole blood viscosity, may be attributed to the presence of various bioactive compounds in the extract that decrease whole blood viscosity. In this regard, previous studies on rats and fish have shown that C. dactylon extract could affect the quantity and quality of red blood cells which are the main factors determining whole blood viscosity (37,38). Some compounds in herbal extracts, such as flavonoids, have been found to increase red blood cell deformability and reduce their tendency to aggregate, allowing them to change shape easily and flow more smoothly through narrow blood vessels, preventing clumping and increasing blood viscosity (39).…”
Section: Discussionmentioning
confidence: 99%
“…The lack of a significant effect of C. dactylon extract on plasma viscosity, while reducing whole blood viscosity, may be attributed to the presence of various bioactive compounds in the extract that decrease whole blood viscosity. In this regard, previous studies on rats and fish have shown that C. dactylon extract could affect the quantity and quality of red blood cells which are the main factors determining whole blood viscosity (37,38). Some compounds in herbal extracts, such as flavonoids, have been found to increase red blood cell deformability and reduce their tendency to aggregate, allowing them to change shape easily and flow more smoothly through narrow blood vessels, preventing clumping and increasing blood viscosity (39).…”
Section: Discussionmentioning
confidence: 99%